Analisis Personal Branding Anya Melfissa Sebagai Vtuber Indonesia di Media Sosial - Muhammad Hendi Al Ishar; Rina Juwita (Jurnal Indonesia : Manajemen Informatika dan Komunikasi, 2024)
Today’s digital technology has developed and can be utilized by its users, one of whom is doing Personal branding by becoming a VTuber (Virtual YouTuber). This research aims to find the Personal branding of an Indonesian VTuber named Anya Melfissa by utilizing YouTube and Twitter/X in her career. This research uses a qualitative method with a qualitative descriptive approach and is based on the Personal branding theory coined by Peter Montoya. Data collection techniques include observation, interviews, and documentation. In the interviews, three informants were obtained using purposive sampling technique. This research uses data analysis techniques from Matthew B. Miles and Michael Huberman. Based on the results of the study, Anya Melfissa’s personal brand has relevance to Peter Montoya’s Personal branding theory, which includes the concepts of specialization, leadership, personality, distinctiveness, visibility, persistence, and goodwill. The results showed that specialization in Anya Melfissa’s Personal branding, which is fluent in Indonesian, English, and Japanese, is the dominant characteristic in her Personal branding.